JIT success in Singapore. - Chen, Wei Cheng. (2008)
The objective of this paper is to investigate the critical factors that affect the success of Just-In-Time (JIT) practices in Singapore. Based on past researches, six factors, namely management support, workers empowerment, supplier relations, production process, quality management and technology infrastructure were identified to investigate its impact on JIT success.